The Role of the Indonesian Government in the Legal Protection of Indonesian Migrant Workers - Rohani, Aceng Asnawi; Gunawati, Anne; Agus, Dede; Romdanah, Siti; Suhadi, Aris; Suryanti, Lili; Fasyehhudin, Mohammad; Candra Jaya, Beni Prawira (Faculty of Law, Universitas Pekalongan, 2024)
Legal protection of Indonesian Migrant Workers continues to be pursued, especially because of the many rights violations and inhumane treatment experienced by some Indonesian Migrant Workers. So that this phenomenon requires serious attention, both at the national and international levels. The purpose of this study is to examine and find out how the legal protection of the rights of Indonesian workers in national and international law and whether the role of the Indonesian government has been implemented in protecting the rights of Indonesian workers abroad. The research method used is normative juridical, with an approach that focuses on law as a system of norms. This system of norms includes the principles, rules, and guidelines of the applicable law, including agreements and theories put forward by experts. This research highlights the government's efforts to build and implement a legal framework to support the rights of Indonesian Migrant Workers. However, there are still challenges that need to be addressed, such as improved monitoring and enforcement to ensure the policy is implemented effectively. This research provides greater insight into the dynamics of the Indonesian government's role in protecting workers' rights, with the aim of making this protection more effective and comprehensive.